Esineiden internet -teknologian hyödyntäminen vihreän rakentamisen liiketoimintamalleissa - Saari, Samu Elias (2024)
With increasing environmental awareness, the construction sector has faced pressure to adopt more environmentally friendly practices. Given its conservative nature and the ever-changing environmental context, the sector finds it challenging to embrace new technologies. This study focuses on the use of the Internet of Things (IoT) in green construction and assesses its value across different aspects of the business model. It examines how IoT technology enhances green building projects from a value creation perspective and seeks to identify potential reasons for the slow technological adoption in the construction sector through an IoT lens. The theoretical component of the study was conducted as a narrative literature review, while the empirical component involved semi-structured thematic interviews with construction industry professionals. IoT significantly benefits green building business models by enhancing transparency and process efficiency, thereby generating both direct and indirect positive environmental impacts. The findings also indicate that although IoT opens new value-creation opportunities in green building processes, broader deployment, and adoption of the technology necessitate a deeper transformation within the construction industry.